Service Failure as Service Quality Indicator for Healthcare During the Pandemic - Mishra, Purna Chandra; Kar, Brajaballav; Kar, Nilamadhab; Jena, Damodar (Prabandhan: Indian Journal of Management, 2025)
Purpose : The COVID-19 pandemic affected the ability of healthcare institutions to deliver quality services. Demand for specific resources, freedom to choose hospitals or doctors, restricted information, and the virulence of the disease caused disruption. The SERVQUAL, as a quality measure in a pandemic disruption, was perceived as debatable in a crisis, and an alternative model was assessed from a service failure (SERVFAIL) perspective. Methodology : Service failure items were collated from the literature. An online structured questionnaire survey sought responses from individuals who accessed hospital services during COVID-19 on their perception of hospital service quality. The SPSS 28 version was used for analysis and included chi-square tests, t-tests, analysis of variance, correlation, and regression. Findings : The scores for each SERVQUAL dimension were close to neutral and thus did not indicate actionable dimensions. Items of SERVFAIL, such as the wait time, item scarcity, and unhelpful staff, were addressable concerns. Demography and exposure to COVID-19 influenced service failure perception. The negative correlation between SERVFAIL measures and SERVQUAL suggested the instrument’s validity. Regression analysis indicated that unhelpful staff and lack of information significantly reduced the perceived service quality. SERVFAIL measures were distinct from SERVQUAL and indicated appropriate actionable areas in this public health emergency. Practical Implications : Service failure information was more actionable and could suggest areas of immediate improvement compared to SERVQUAL items. The scores can facilitate management decision-making. Originality : SERVFAIL was an innovative conceptualization compared to SERVQUAL. Second, the comparison between the two in healthcare service delivery in a health crisis was unique to this study.